Impactos de reservatório de usinas hidrelétricas sobre a comunidade arbórea de florestas estacionais - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
Dams construction can change the composition and structure of forests located on the shores of the artificial lake. The objective of this study was to evaluate the intensity of changes in the floristic and structural composition of two seasonal forests, one deciduous and one semideciduous. These forests were located distant from water resources and now are near the artificial lake created by a dam at its margin. Forest monitoring were carried out using the permanent plots method in 2006 (T0), 2008 (T02), 2010 (T04) and 2016 (T10) of all trees with a circumference at breast height (1.30 m) greater than or equal to 15 cm (CAP ≥ 15) and calculated dynamics rates (Mortality, Recruitment, Increase, Decrement, Turnover and Net Change), the diversity and the estimated richness of each area along the measurement times. There was increase in the richness, diversity and basal area of the two forests. All the dynamics rates were higher in the Decidual Forest, comparing the initial time (T0) with the last measurement time (T10), showing greater instability in this forest than in the Semideciduous Forest. The deciduous forest presented more modifications after damming, however with loss of trees after 10 years of impact. The negative balance occurred due to the high mortality rate of species typical from dry environments that were much higher in relation to the recruitment of trees from species commonly found in humid forests. Changes in both forests were large; similars or greaters in relation to those changes occurring due to large scale impacts such as floods and fires. However, unlike transitory impacts, where the forest can return to its normal equilibrium state, the changes caused by the reservoir at the forest shorelines can be considered non-transitory and alter the successional paths typical of a seasonal forest.
Keywords: Taxas de dinâmica; Riqueza de espécies; Matas secas; Efeito ripário; Dynamic rates; Species richness; Dry woods; Riparian effect; CIENCIAS AGRARIAS